The forms of Political Participation in General Elections by Beginner Voters - Aulia Sholichah Iman Nurchotimah (Universitas of Muhammadiyah Makassar, 2020)
Abstract. Democracy as a government system in Indonesia is certainly closely related to the General Election. Participating in the implementation of a democratic system is a form of participation as citizens. Any activity that relates to participation in politics can be manifested in various forms. A beginner voter is a person who firstly participates in general election activities whether it is in the legislative election, presidential election, and local leader elections. Beginner voters become parties that must be considered or must be really paid attention to because they influence decision making. Beginners voters are also parties who have dynamic personal characteristics, which will influence their forms of political participation. The purpose of this study was to explore forms of political participation of beginner voters in general elections. Researcher used a qualitative approach and descriptive qualitative as the data analysis technique. The data which were used in this research were primary and secondary data. Data collection techniques were observation, interviews, and documentation. The results showed that the forms of political participation of beginner voters in the general election were voting, joinning campaign activities, participating in political discussion, understanding various political and social issues by following political news both internally and externally through the mass media, obeying the government, accepting, and implementing government decisions, submitting criticisms, and making improvements to rectify policies.Keywords: Political Participation; General Election, Beginner VoterAbstrak. Demokrasi sebagai sistem pemerintahan di Indonesia tentunya sangat berkaitan dengan Pemilihan Umum. Ikut serta dalam pelaksanaan sistem demokrasi adalah wujud dari partisipasi sebagai warga negara. Suatu kegiatan berpartisipasi dalam politik, dapat diwujudkan dengan berbagai bentuk. Pemilih pemula merupakan seseorang yang pertamakali mengikuti kegiatan berbagai bentuk partisipasi politik pemilihan umum yang dilakukan diantaranya mengikuti pemilihan umum legislatif ataupun pemilihan pemimpin rakyat baik Presiden dan Wakil Presiden maupun Gubernur atau Bupati. Pemilih pemula menjadi pihak yang harus diperhatikan karena berpengaruh dalam pengambilan keputusan. Pemilih pemula juga merupakan pihak yang memiliki karakterisitik pribadi yang dinamis, yang akan mempengaruhi dari bentuk-bentuk partisipasi politiknya. Penelitian bertujuan untuk mengetahui lebih dalam terkait berbagai bentuk kegiatan partisipasi politik yang dilakukan oleh pemilih pemula dalam suatu kegiatan pemilihan secara umum. Penelitian ini menggunakan pendekatan kualitatif. Sumber data dalam penelitian ini mengambil sumber sekunder dan primer. Metode dalam mengumpulkan data diantaranya melakukan wawancara, kemudian observasi serta dokumentasi. Berbagai bentuk partisipasi dalam politik yang dilakukan oleh pemilih pemula dalam pemilihan umum yaitu mengikuti pemungutan suara, ikut serta dalam suatu kampanye politik dalam pemilihan umum, melakukan suatu diskusi mengenai politik dalam pemilihan umum, mengikuti berbagai berita politik dan pemilihan umum melalui media massa, patuh dalam rangka menjalankan aturan dari pemerintah serta ikut serta dalam upaya mengkritik pemerintah demi kebaikan bersama.Kata Kunci: Partisipasi dalam Politik;Pemilihan Umum; Pemilih Pemula